Kunst voor Convent 22 : Veilingscatalogus. - De Schryver, Elke (S.l. : vzw Autimismus : VDAB, 2016)
Verwee, Adriaan ; Maes, Agnes ; Biltereyst, Alain ; Michels, Alex ; Honnay, André ; Wenzel, Anne ; du Bois, Arpais ; Hamelryck, Ado ; Van Rossem, Bert ; Loerakker, Bert ; Depuyt, Bieke ; Van Breedam, Camiel ; Vanderlinden, Carole ; Verhelst, Christian ; Wright, Cindy ; Waeghe, Colin ; Todorova, Denitsa ; Mahieu, Didier ; Meijer, Dave ; Zoete, Dirk ; Berkvens, Elise ; Littwitz, Ella ; De Smet, Erik ; Van Gestel, Fik ; Van Hiel, Frank ; Eerdekens, Fred ; Geurts, Frederic ; Van Dijck, Hannelore ; Everaert, Hans ; Op De Beeck, Hans ; Van De Kerckhove, Hans ; Brouckaert, Hedwig ; d'O, Honoré ; Bytebier, Jean-Marie ; Bilquin, Jean ; Massart, Jean-Georges ; De Smedt, Jo ; Van Rijckeghem, Jo ; De Wit, Johan ; De Wilde, Johan ; Raes, Joke ; Juchtmans, Jus ; Mouton, Jef ; Vanhee, Klaas ; Broucke, Koen ; Claus, Luc ; Hoeckx, Luc ; Nollet, Lieven ; Nagtzaam, Marc ; Marcase ; De Brabandere, Mario ; De Muysere, Marie-Ange ; Cloet, Marc ; Aerts, Michael ; Slangen, Nancy ; Ervinck, Nick ; Demoen, Nikolaas ; Gees, Paul ; Van Gysegem, Paul ; De Cupere, Peter ; Morrens, Peter ; Wauters, Peggy ; Aguirre Y Otegui, Philip ; Nicolodi, Renato ; De Boe, Rik ; Westphal, Sara ; Van Grinsven, Servi ; Muller, Sofie ; Voets, Sjef ; Leblon, Stephanie ; Baelen, Steven ; Desmet, Stief ; Van Bergen, Thé ; Bogaert, Thomas ; Vosters, Vadim ; De Roder, Vincent ; Bailly, Virginie ; De Sauter, Willy
Kunst voor Convent 22, VAC - Virginie Lovelinggebouw, Gent, 22.11.2016
boek